Comparison of Subjective Wellbeing and Positive Future Expectations in Between Working and Nonworking Adolescents in Turkey - KARAKOÇ, AYŞE; BAYRI BİNGÖL, FADİME; KARACA, SEMRA (ZAMENSALAMATI PUBL CO, 2016)
Background: Wellbeing is one's evaluation and judgment of one's life. It consists of 3 dimensions: positive affectivity negative affectivity, and life satisfaction. Objectives: This study aimed to compare the subjective wellbeing and positive future expectations between working and nonworking adolescents. Patients and Methods: The study was designed as descriptive and comparative. The study sample consisted of 420 working and 482 nonworking adolescents (n = 902) aged 15-20 years, who were randomly recruited from two occupational education centers in Istanbul, Turkey and two high schools (formal educations) in the same district. Results: Adolescent subjective wellbeing scale (ASWS) total mean (SD) scores for working adolescents and nonworking adolescents were 48.76 (9.50) and 49.72 (8.01), respectively. In addition, positive future expectations scale (PFES) total mean (SD) scores for working adolescents and nonworking adolescents were 18.71(4.50) and 19.06 (3.49), respectively. In this study, no significant difference was found between the general wellbeing (scale total median score) scores of the working and nonworking adolescent groups (Z=1.01, P = 0.315). However, significant differences were found in the family relations satisfaction (Z=3.23, P = 0.002) and relations with significant others (Z=2.85, P = 0.004) subscales of the ASWS. Conclusions: A positive relationship was found between adolescent subjective wellbeing and positive future expectations. It was found that nonworking adolescents scored higher on the dimensions of family relations and relations with significant others of subjective wellbeing compared to those dimensions in working adolescents.
Keywords: Adolescence; Wellbeing; Future Expectation; Occupational Education; Formal Education; PERSONALITY; HAPPINESS; EMPLOYMENT; GENDER; FAMILY; IMPACT